INDEKS HAMMING PADA GRAF OPERASI PERKALIAN KORONA DAN PERKALIAN KARTESIAN YANG DIBANGUN MATRIKS INSIDEN - Lolyta Damora Simbolon (Universitas Islam Sumatera Utara, 2023)
Suppose a finite simple graph is represented in the incidence matrix B. Each row in matrix B is a sequence of binary numbers with finite length. The Hamming distance of two vertices and of a simple graph G is defined as the number of positions of different digits. The Hamming index of a simple graph is the sum of the Hamming distances for all the different points in the graph. Suppose that each and is a simple graph whose degree is almost uniform. Using the Hamming Index, we obtain a formula for the Hamming Index on a graph in the form of corona multiplication and cartesian multiplication with each of the two graphs being of almost uniform degree.